Rainbow trout integrated response after recovery from short-term acute hypoxia - García-Meilán, Irene; Tort, Lluis; Khansari, Ali Reza (Frontiers in Physiology, 2022)
Overcoming a stress situation, such as hypoxia episodes, which involve an allostatic load, will depend on the ability of fish to modulate physiological and biochemical systems to maintain homeostasis. The aim of the study was to determine the integrated stress response after acute hypoxia of rainbow trout considering the different elements and areas of the stress response: systemic and mucosal, local and global, from the systemic HPI axis to skin mucosa. For this purpose, trout were subjected to acute hypoxia (dissolved O2 down to 2 mg/L) for one hour and then recovered and sampled 1, 6 and 24h after reoxygenation. Physiological responses were significantly affected by hypoxic stress and their interaction with time after the challenge, being significant for plasma lactate and cortisol levels, in both plasma and skin mucus. At central brain level, only trh expression was modulated 1h after hypoxia which indicates that brain function is not heavily affected by this particular stress. Unlike brain, head kidney and skin were more affected by hypoxia and reoxygenation. In head kidney an upregulation in expression of most of the genes studied (gr, il1β, il6, tgfβ1, lysozyme, caspase 3, enolase, hif-1, myoglobin, sod2, gpx, gst and gsr) took place 6h after recovery, whereas only hsp70 and il10 were upregulated after 1h. On the contrary, in skin most of the analyzed genes showed a higher upregulation during 1h after stress suggesting that in the skin a local response took place as soon as the stressor was detected, thus indicating the importance of the skin in the building of a stress response, whereas the interrenal tissue participated in a later time point, to help preventing further alteration at central level. The present results also show that, even that the stressor is a physical/environmental stressor, all components of the biological systems participate in the regulation of the response and the recovery process, including neuroendocrine, metabolism and immunity.